Unravelling the influence of advection and diffusion on the spatial and temporal evolution of pollutant concentration - Norazaliza, Mohd Jamil; Khan, Ilyas (Semarak Ilmu Publishing, 2024)
The spatial distribution and temporal evolution of pollutant concentration are complex phenomena. Advection and diffusion are the primary drivers influencing the dynamic of pollutant concentrations. This paper aims to investigate and elucidate the roles of advection and diffusion on pollutant concentration's spatial and temporal evolution in a one-dimensional domain. The finite element method (FEM) is used to solve the governing equation numerically. The underlying concepts of FEM hand-to-hand with MATLAB software were presented. The simulation study revealed that advection and diffusion uniquely impact the system's dynamic. Advection, driven by the bulk movement of water, leads to rapid and long-range transport of pollutants, while diffusion, driven by random molecular motion, causes more gradual dispersion. The interplay between these processes is a critical determinant in understanding the overall behaviour of pollutant concentrations over time and space.